The Constitutional Boundaries of European Fiscal Federalism: A Study of Public Finance Governance in the European Economic and Monetary Union - Gordon, Brady (School of Law. Discipline of Law, 2018)
The first principal task of this research undertaking is to identify the constitutional boundaries of fiscal federalism that are integral to the stability of the European Union legal order as a whole. The second principal task of this research is to define which institutional configurations of fiscal federalism theory remain compatible with the boundaries of the European legal order in this area of study. The analysis yields two constitutional criteria with which any model of European fiscal federalism must comply if it is to remain stable and permanent as a matter of law and economics: First, any model of European fiscal federalism must preserve the fiscal sovereignty of the twenty-eight constitutional democracies which form the basis of its legal order. Not only has economic policy not been conferred on the Union, it cannot ever be so conferred without abrogating, inter alia, the Democratic State shielded by the ‘eternity clause’ (Articles 20 and 79(3)) of the German Basic Law. Numerous other constitutional courts have drawn similar boundaries around fiscal sovereignty. In so far as the limits of EU competence are governed by the principle of conferral, it can have no powers other than what the Member States have given it, and nemo plus iuris transfere (ad alium) potest quam ipse habet, what the Member States have given it is limited by their own ‘constitutional identity’ jurisdictions. Second, hard budget constraints and market discipline are indispensable requirements for the fundamental guiding principles of price stability and fiscal discipline binding on the mandate for EMU under Articles 119-127 TFEU. Systems of fiscal federalism which substitute hard budget constraints for centralised legal governance are not compatible with the guiding principles of price stability and fiscal discipline, and are not compatible with the immutable constraints of fiscal sovereignty underlying the European legal order. In particular, the German Constitutional Court has held that the ‘no bailout’ and ‘no monetary financing’ rules safeguard the Bundestag’s ‘national budgetary responsibility,’ and Germany’s constitutional identity would be violated if the Stabilitätsgemeinshaft should become a ‘liability community’ through the ‘direct or indirect communitarisation of state debts.’ This study concludes that the European Union has embarked upon a model of ‘fiscal union’ that is manifestly incompatible with the European legal order. It concludes by offering a roster of specific amendments to defuse latent conflicts under existing legislation, and by specifying the criteria which European fiscal federalism must meet in order to remain stable and permanent as a matter of law and economics.
Keywords: European Union Law; Constitutional Law; European Sovereign Debt Crisis; Fiscal Federalism; European Monetary Union